PEMANFAATAN MEDIA PEMBELAJARAN PESERTA DIDIK SEKOLAH DASAR DALAM MENCAPAI TUJUAN INTRUKSIONAL - Ucha Jr, Gabriella Vallencia; Dandi Putra, Hafizh; Irfannisa, Iffa; Kinasih, Milka Sekar (STP St. Bonaventura Medan, 2024)
Learning is an interaction between educators and students to achieve educational goals. Effective learning can facilitate students so that it can support the achievement of the expected learning objectives. Successful learning must be able to adjust the needs of each student by looking at every important aspect needed, such as the learning media that will be used. Learning media is a tool or means used to convey information in order to achieve learning objectives. This study aims to find out the use of media for learning so that instructional goals are achieved in order to increase student learning competencies. The media made by the teacher must be relevant to the material to be taught so that it can easily assess the extent to which the learning objectives have been achieved. However, it is necessary to know that learning media has every advantage and disadvantage in achieving instructional goals. Through this research, it is hoped that teachers need to pay attention to what students really need in order to achieve instructional goals that maximize behavioral goals.